Pemberdayaan Pelaku Usaha Mikro Oleh Dinas Koperasi dan Umkm di Kota Pekanbaru - Fiko Fernando; Khairul Amri (Lembaga Pengembangan Kinerja Dosen, 2023)
The background of this research is that some micro business actors have been out of business due to the pandemic, and only a small number of micro business actors have been empowered by the Pekanbaru City Cooperatives (diskop) and UMKM Office. This study aims to: (1) find out how the empowerment of micro-enterprises by Diskop and UMKM in Pekanbaru City; and (2) knowing the factors that influence the empowerment of micro business actors by Pekanbaru's Diskop and UMKM. This type of research is qualitative research. There were six informants in this study, and one key informant. The results of this study are: (1) the empowerment of micro-entrepreneurs by the Diskop and UMKM in Pekanbaru City has fulfilled the aspects of good empowerment, because there are already aspects of enabling, empowering, and protecting. The enabling aspect is known from the efforts to collect data on the potential of micro-entrepreneurs. Then the empowering aspect is known from the activities of forming business partnerships, empowering business institutions, coordinating and synchronizing micro business actors with regional stakeholders. Meanwhile, the aspect of protecting is protecting micro-enterprises from adverse events resulting from medium and large business actors through legal protection and advocacy assistance; (2) the empowerment of micro business actors by the Diskop and UMKM in Pekanbaru City is known from two factors, namely internal factors and external factors. Internal factors are factors originating from the Pekanbaru City Diskop and UMKM, such as the limited budget for empowering micro-entrepreneurs. External factors are related to micro business actors, such as the desire to be empowered but not empowered by the Office. In addition, there are some micro business actors who do not support empowerment activities carried out by the office, because they are considered to be less needed by micro business actors. The research suggestions are: (1) micro-entrepreneurs should be given socialization regarding the importance of participating in various empowerment programs by the Pekanbaru City Diskop and UMKM; (2) the importance of increasing the implementation budget for various micro business empowerment activities so that many micro business units can be empowered.